2007
DOI: 10.1242/dev.010397
|View full text |Cite
|
Sign up to set email alerts
|

A wave of EGFR signaling determines cell alignment and intercalation in theDrosophilatracheal placode

Abstract: Invagination of organ placodes converts flat epithelia into three-dimensional organs. Cell tracing in the Drosophila tracheal placode revealed that, in the 30-minute period before invagination, cells enter mitotic quiescence and form short rows that encircle the future invagination site. The cells in the rows align to form a smooth boundary ('boundary smoothing'), accompanied by a transient increase in myosin at the boundary and cell intercalation oriented in parallel with the cellular rows. Cells then undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 50 publications
6
108
1
Order By: Relevance
“…Previous work examining tracheal morphogenesis in the fly has demonstrated that interfaces between cells with low levels versus high levels of EGFR signalling correlate with MyoIIdependent AJ remodelling in the tracheal placode (Nishimura et al, 2007). This situation resembles that which we describe here in the wake of the MF.…”
Section: Research Articlesupporting
confidence: 80%
See 1 more Smart Citation
“…Previous work examining tracheal morphogenesis in the fly has demonstrated that interfaces between cells with low levels versus high levels of EGFR signalling correlate with MyoIIdependent AJ remodelling in the tracheal placode (Nishimura et al, 2007). This situation resembles that which we describe here in the wake of the MF.…”
Section: Research Articlesupporting
confidence: 80%
“…Supra-cellular cables of MyoII have been previously associated with cell alignment in various epithelia (Nishimura et al, 2007;Simone and DiNardo, 2010;Walters et al, 2006) and have also been observed at the boundary of sorted clones, whereby cells align at a MyoII-enriched interface (Chang et al, 2011;Le Borgne et al, 2002;Wei et al, 2005). Interestingly, we find that the actomyosin cable defining the posterior boundary of the MF is also preferentially enriched for Rok, a component of the T1, MyoIIpositive AJ in the ventral epidermis (Simoes Sde et al, 2010).…”
Section: Compartment Boundary and Cell Intercalation During Retina Mosupporting
confidence: 72%
“…Actomyosin cables are also characteristic of additional processes, e.g. dorsal closure and germband extension in the Drosophila embryo Blankenship et al, 2006), tracheal tube invagination and neural plate bending and elongation (Nishimura et al, 2007;Nishimura and Takeichi, 2008), and wound healing (Martin and Lewis, 1992;Wood et al, 2002). During Drosophila germ band extension, it has been shown that mechanical tension is higher at cell bonds that are part of an actomyosin cable compared with isolated cell bonds, indicating that cell bond tension is influenced by higher-order cellular organization during this process (Fernandez-Gonzalez et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They then re-enter mitosis and undergo one last round of cell division towards the end of the invagination process. The orientation of the cell division axis is biased towards the center of the tracheal pit and might help to direct cells to flow into the site of invagination (Nishimura et al, 2007). (B) A model of the signaling and cell remodeling events required for ordered tracheal cell invagination.…”
Section: Introductionmentioning
confidence: 99%
“…It is partly suppressed dorsally by the expression of sal (also known as spalt), which encodes a zinc finger transcription factor, leading to the observed asymmetry in invagination along the dorsoventral axis. In addition, the careful examination of cell behaviour and myosin localization during the invagination process has revealed that the Egf pathway is activated in a wave, which extends from the centre of the placode, where cells initially constrict apically, to the outer cells, coordinating the timing and positioning of intrinsic cell internalization activities (Nishimura et al, 2007). Egfr signalling eventually translates into an ordered apical distribution of actin and myosin, which presumably generates the forces that lead to invagination via actomyosin contraction.…”
mentioning
confidence: 99%